HUMAN PHILOSOPHY IN THE TEACHING OF NASAFI - Narziyev Zubaydillo Ibodilloyevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The issue of man is one of the most important topics in the teachings of Sufism. This article is devoted to the views of the Sufi and philosopher Aziziddin Nasafi on human philosophy and existence, and human philosophy is analyzed on the basis of his works. The article also provides a philosophical analysis of Nasafi's views on human existence.